Everything Changed When Lola Arrived. Edulab: a Space to Learn in Freedom (2018)
This is the story of what brought with it the arrival of Lorena Avilés, Spanish teacher, to the Jesús Amigo school in the 12th of October neighborhood, she achieves, with the help of the students, after thinking of an education more in accordance with their interests, to create the EduLab, a collective learning space in which all kinds of innovations were generated , creations and friendships.